PEDAGOGIC DIAGNOSTIC METHODS OF JUVENILE CONVICTS SOCIAL HEALTH: EXPERIMENTAL STUDY - Ganishina, Irina; Podnebesnaya, Ella; Mamedova, Albina; Tyugaeva, Nina; Tkachenko, Nikolay; Ovsyannikova, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Convicts social health is regarded by the authors of the article as the state of social welfare including the ability to support the socially healthy relationships in the society. To diagnose this state of ability among the juvenile convicts serving sentences in the correctional colonies is of special importance. According to the experimental study there is not enough work done to develop social health among juvenile convicts in the places where the imprisoned are stayed. The hypothesis of the investigation is the assumption that to form the social health among convicted male minors in the juvenile correctional facility will be more successful if they participate in the project “Book is the source of new life and the way to rehabilitation.” To diagnose the state of social health of juvenile convicts the following methods and techniques have been used, they are watching, talking, summative assessment, formative assessment, testing, The Test of Viability by D.A. Leontyev, The Questionnaire: Health, Activity, Mood (by V.A. Doskin, N.A. Lavrentyeva, V.B. Sharay, M.P. Miroshnikov); Success Stimuli and Failure Fear methods by A.A. Rean. The summative assessment procedure was held in March 2019, the formative assessment experiment had been conducted for 3 months (from April till June 2019). The summative assessment has shown that juvenile convicts have weak viability, reduced level of well-being, and activity, and mood as well; there is a low level of success stimuli and high level of failure fear. The results of formative assessment have shown that the participation in the Project helps to form viability, activity, cheering up, decreasing of failure fear, increasing of success motivation; and it assists conforming social health of juvenile convicts as a whole.